1984
DOI: 10.1017/s0022029900023414
|View full text |Cite
|
Sign up to set email alerts
|

Reviews of the progress of Dairy Science: Long term effects of plane of nutrition on the performance of the dairy cow

Abstract: This is regarded as the prolongation of the effects of differential feeding after this itself has ceased. Compensatory effect Supernormal performance on re-alimentation following a period of underfeeding, as with growing stock, is included in this category. Buffering effect This is regarded as the cow's ability to counter nutritional insults by withdrawal of body reserves to support milk production. Total effect This is the summated effect over the total period of application of differential feeding. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 173 publications
6
42
0
2
Order By: Relevance
“…In certain trials (Kennedy et al, 2007;Roche, 2007), the authors describe a significant carryover effect on milk and fat yield, but its persistence is actually rather limited (1 to 2 months). The amplitude and duration of this delayed effect depend initially on the importance of the main effect of the treatment and the observed duration of the carryover effect (Broster and Broster, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In certain trials (Kennedy et al, 2007;Roche, 2007), the authors describe a significant carryover effect on milk and fat yield, but its persistence is actually rather limited (1 to 2 months). The amplitude and duration of this delayed effect depend initially on the importance of the main effect of the treatment and the observed duration of the carryover effect (Broster and Broster, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The present study is consistent with this view that peak yield substantially sets the performance of the whole lactation; both peak yield and total lactation yield was greater in the right gland by the same percentage. Clearly peak yield was not uniquely determined by genetic factors (Broster & Broster, 1984) but may be influenced by the animal's treatment during early lactation. In the present study peak, but not persistency, was locally controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The stage of lactation can affect the magnitude of milk response to supplements because energy is partitioned more towards BCS and less towards milk synthesis as lactation progresses (Broster & Broster 1984). It has been reported that the immediate milk response to supplements was greater in early lactation, decreasing thereafter (Stockdale et al 1998;Kellaway & Harrington 2004).…”
Section: Stage Of Lactationmentioning
confidence: 99%